Inhibition of Small-Conductance Calcium-Activated Potassium Current (IK,Ca) Leads to Differential Atrial Electrophysiological Effects in a Horse Model of Persistent Atrial Fibrillation - Fenner, Merle Friederike; Gatta, Giulia; Sattler, Stefan; Kuiper, Marion; Hesselkilde, Eva Melis; Adler, Ditte M. T.; Smerup, Morten; Schotten, Ulrich; Sørensen, Ulrik; Diness, Jonas Goldin; Jespersen, Thomas; Verheule, Sander; et al. (Frontiers in Physiology, 2021)
Background: Small-conductance Ca2+-activated K+ (KCa2) channels have been proposed as a possible atrial-selective target to pharmacologically terminate atrial fibrillation (AF) and to maintain sinus rhythm. However, it has been hypothesized that the importance of KCa2 current – and thereby the efficacy of small-conductance Ca2+-activated K+ current (IK,Ca) inhibition – might be negatively related to AF duration and the extent of AF-induced remodeling. Experimental Approach and Methods: To address the hypothesis of the efficacy of IK,Ca inhibition being dependent on AF duration, the anti-arrhythmic properties of the IK,Ca inhibitor NS8593 (5 mg/kg) and its influence on atrial conduction were studied using epicardial high-density contact mapping in horses with persistent AF. Eleven Standardbred mares with tachypacing-induced persistent AF (42  5 days of AF) were studied in an open-chest experiment. Unipolar AF electrograms were recorded and isochronal high-density maps analysed to allow for the reconstruction of wave patterns and changes in electrophysiological parameters like atrial conduction velocity and AF cycle length. Atrial anti-arrhythmic properties and adverse effects of NS8593 on ventricular electrophysiology were evaluated by continuous surface ECG monitoring. Results: IK,Ca inhibition by NS8593 administered intravenously had divergent effects on right and left AF complexity and propagation properties in this equine model of persistent AF. Despite global prolongation of AF cycle length, a slowing of conduction in the right atrium led to increased anisotropy and electrical dissociation, thus increasing AF complexity. In contrast, there was no significant change in AF complexity in the LA, and cardioversion of AF was not achieved. Conclusions: Intra-atrial heterogeneity in response to IK,Ca inhibition by NS8593 was observed. The investigated dose of NS8593 increased the AF cycle length but was not sufficient to induce cardioversion. In terms of propagation properties during AF, IK,Ca inhibition by NS8593 led to divergent effects in the right and left atrium. This divergent behavior may have impeded the cardioversion success.